Simulation-Based Allocation of the Inspection Stations in the Production Line for Production Cost Optimization - Al-Baldawi, Zainab; Sabah, Ayat; Sabeeh A. Al-Zubaidi, Sawsan (Engineering, Technology & Applied Science Research, 2025)
Due to increasing competition, companies pursue achieving a maximum production rate with minimal defects in order to saving costs by minimizing the production costs while maintaining high product quality to stay competitive in the markets. The assurance of a high-quality product by inspection of conformity is an important issue. The inspection process plays a crucial role in detecting and eliminating the causes of defects at an early stage, reducing the percentage of defective products and minimizing production costs. In this paper, an allocating algorithm is proposed and a mathematical allocating model is developed to investigate and determine the optimal number and locations of inspection stations along the production line where the proposed model aims to balance the expected cost of defects with the cost of inspection stations to achieve minimum total cost. The proposed model was practically applied to a leather jacket production line. The final results show that two allocation solutions can be adopted. The first is the allocating solution of the proposed model that proposed 23 inspection stations, resulting saving cost 582,839 IQD while, the second solution is derived from the first solution that based on considering only inspection stations that achieve maximum saving cost so,7 inspection stations were allocated, achieving total saving cost of 552,545 IQD.